DOP15 Metabolomics coupled with pathway analysis characterise metabolic changes in treatment-naive ulcerative colitis patients. (25th January 2019) - Diab, J; Hansen, T; Goll, R; Jensen, E; Moritz, T; Florholmen, J; Forsdahl, G
Abstract: Background: Metabolomics, defined as the large-scale assessment of small molecules, known as metabolites, is a powerful tool in understanding complex inflammatory disease. This approach has been applied to study immune-mediated diseases such as rheumatoid arthritis, psoriasis, and diabetes mellitus. However, there are few studies describing the metabolomic profile in inflammatory bowel disease (IBD) patients. Therefore, our study aims to identify the main metabolic alteration in newly diagnosed treatment-naïve ulcerative colitis (UC) patients compared with UC patients in deep remission and healthy controls. Methods: Colon mucosa biopsies were taken from 22 treatment-naive UC patients at the debut of the disease (inflamed mucosa), 14 UC patients in deep remission, and 15 healthy subjects. The degree of inflammation and state of remission were assessed by endoscopy, histology, and by measuring TNF gene expression. Metabolomics analysis of the colon biopsies was performed by ultra-high-performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS-MS). In total, 140 metabolites from 33 metabolic pathways (Kyoto Encyclopedia of Genes and Genomes database KEGG) were identified. Results: Mucosal levels of 17 metabolites were significantly changed in treatment-naive patients with respect to controls, whereas mucosal levels of 7 metabolites were significantly changed in deep remission patients compared with healthy controls. The most prominent changes were in Omega-6 arachidonic acid phospholipids, namely phosphatidylcholine (PC20:4) and phosphatidylethanolamine (PE20:4). Pathway enrichment analysis revealed disruption in six metabolic pathways. Pathway topology analysis revealed that UC is associated mainly with altered tryptophan and omega-6 linoleic acid metabolism pathways. Furthermore, high mucosal TNF mRNA levels were correlated with changes in the omega-6 arachidonic acid metabolism pathway. Conclusions: To the best our knowledge, this is the first study describing metabolomic profiles in colon mucosa of untreated newly diagnosed and deep remission UC patients. We have identified main metabolic pathways that might be involved in the UC onset. These pathways may present diagnostic biomarker or monitoring tools in UC. In addition, these metabolic fingerprints may suggest potential therapeutic targets.